O capital estrangeiro na área da saúde: uma perspectiva crítica - Santos Filho, Vicente Arouche (2018)
The objective of this research is to explain and understand the implications of changing legislation regarding the release of foreign capital in public health care. Health policy was shaped by the 1988 Constitution to meet all Brazilians and has undergone several changes over the last 30 years, in which public spending has been surpassed by private spending with the introduction of health insurance regulations and with the permission of the presence of foreign capital in this area, besides the existence of problems of underfunding of the Unified Health System (SUS) by the budgetary mechanisms that prioritize the payment of interest on public debt. This paper exposes the process of development of neoliberalism in Brazil that can be understood as the scenario for identifying the problems of the implantation of the SUS and for the growth of the private sector in the health area. The focus of this study is the introduction of Federal Law 13.097, which allows the entry of foreign capital from the health care area in the country, highlighting the controversy about its introduction